Head and neck hemangiopericytoma in a child: case report - Carvalho, Jomar Rezende; Haddad, Leonardo; Leonhardt, Fernando Danelon; Marques Filho, Marcílio Ferreira; Santos, Rodrigo de Oliveira; Cervantes, Onivaldo; Abrahão, Márcio (São Paulo Medical Journal, 2004)
CONTEXT: Hemangiopericytoma is a relatively rare tumor, first described in 1942, with approximately 300 cases described in the literature to date. In most cases, it affects the trunk and lower extremities. The head and neck incidence is less than 20%, mostly in adults. We describe a case of malignant head and neck hemangiopericytoma in a child. TYPE OF STUDY: Case report. CASE REPORT: A twelve-year-old male patient noted the presence of a firm painless right-side retroauricular lymph node of 1 cm in diameter, which at first remained unchanged for six months, but subsequently enlarged progressively. He denied having had previous trauma at that site. In November 2000, he presented nasal obstruction and voluminous epistaxis that required hospitalization and blood transfusion. During dental treatment one month later, a cranial x-ray revealed bone alterations. A subsequent computed tomography scan showed an extensive lesion of soft tissue density that had invaded the maxillary fossa, eroding the skull base and middle and nasal fossa. The child was then referred to our service, where biopsy was performed, giving a diagnosis of hemangiopericytoma. Shortly afterwards, magnetic resonance imaging revealed that this lesion had undergone significant growth, while maintaining the same invasion pattern. The patient was submitted to conservative surgery in April 2001, with only partial resection of the tumor because of its extent. Histopathological examination of the specimen confirmed the presence of malignant hemangiopericytoma. Following the surgery, the patient presented fast regrowth of the lesion, with partial response to chemotherapy and radiotherapy.